2004
DOI: 10.1520/jfs2003175
|View full text |Cite
|
Sign up to set email alerts
|

The Extraction and Infrared Identification of Gamma-Hydroxybutyric Acid (GHB) from Aqueous Solutions

Abstract: The chemical analysis of gamma-hydroxybutyric acid (GHB) in most forensic laboratories is complicated by the highly polar nature of the GHB molecule, which makes it unsuitable for direct analysis by gas chromatography (GC). Consequently, a popular analytical approach is to convert GHB into the corresponding lactone or a derivative compound that is then identified by mass spectrometry employed in conjunction with GC (GC/MS). An alternative approach is presented here where GHB may be isolated as a free acid spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 18 publications
2
34
0
Order By: Relevance
“…Chappell et al . also reported that the use of n ‐hexane as the extraction solvent gave low recoveries of γ ‐hydroxy butyric acid during a liquid–liquid extraction, further supporting the idea of polar oxylipins and their minimal role in determining CSH.…”
Section: Resultsmentioning
confidence: 81%
“…Chappell et al . also reported that the use of n ‐hexane as the extraction solvent gave low recoveries of γ ‐hydroxy butyric acid during a liquid–liquid extraction, further supporting the idea of polar oxylipins and their minimal role in determining CSH.…”
Section: Resultsmentioning
confidence: 81%
“…The chemistry of GHB in aqueous solution is conditioned by a double equilibrium. On one hand, the cyclization reaction to yield the lactone (GBL) and, on the other, the acid/base equilibrium in which the carboxylic acid form is dissociated into the ionic form with a pK a = 4.6 [21]. The conversion speed into lactone is a relatively slow process in moderately acidic media and it requires a time frame of hours at pH ≥ 2 [22].…”
Section: Methodsmentioning
confidence: 99%
“…This general appearance is consistent with that expected for PB, which has the stronger intermolecular and intramolecular hydrogen bonds due to the higher contents of carboxylic and hydroxyl groups. After reaction, the characteristic bond at 968 cm −1 ascribed to trimethyl quaternary ammonium diminished and a prominent feature at 1593 cm −1 attributed to the presence of the carbonyl‐stretching mode appeared . Also, bands at 1300–1500 got more intense which was attributed to the in‐plane deformation of the carboxyl hydrogen and stretching of the carbon–oxygen bond in the carboxyl group.…”
Section: Resultsmentioning
confidence: 67%